2012
DOI: 10.1021/jf205213n
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Heat-Induced Aggregates of Whey Protein Isolate

Abstract: The effects of heat induced denaturation and subsequent aggregation of Whey Protein Isolate (WPI) solutions on the rate of enzymatic hydrolysis was investigated.Denaturation of whey proteins was monitored by reversed-phase and size exclusion HPLC and observed by native-and SDS-PAGE. Treated and un-treated WPI solutions (100 g L -1 protein) were hydrolysed to a target degree of hydrolysis (DH) of 5 % with Corolase ® PP. Aggregate formation was monitored using light microscopy, with size distribution determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 39 publications
4
52
0
2
Order By: Relevance
“…As a result of changes in protein structure, the profile of peptides released may differ as digestive enzymes may be capable of digesting these regions of the protein that were previously inaccessible to the enzyme. This has been previously shown to be the case for whey protein [121][122]. Furthermore, ACE inhibitory peptides from whey protein isolates (WPI) pretreated at 65 °C were shown to have greater inhibitory activity than peptides from WPI pretreated at 95 °C.…”
Section: Hypotensive Peptides As Functional Food Ingredientsmentioning
confidence: 66%
“…As a result of changes in protein structure, the profile of peptides released may differ as digestive enzymes may be capable of digesting these regions of the protein that were previously inaccessible to the enzyme. This has been previously shown to be the case for whey protein [121][122]. Furthermore, ACE inhibitory peptides from whey protein isolates (WPI) pretreated at 65 °C were shown to have greater inhibitory activity than peptides from WPI pretreated at 95 °C.…”
Section: Hypotensive Peptides As Functional Food Ingredientsmentioning
confidence: 66%
“…Therefore, endo-protease activity can be affected by the degree of protein denaturation where a positive influence on hydrolysis reaction rates has been demonstrated in individual protein fractions (Guo, Fox, Flynn & Kindstedt, 1995;Schmidt & van Markwijk, 1993) and heterogeneous concentrates (Kim et al, 2007a). Kim et al (2007a) reported that a prehydrolysis heat-treatment (100 ºC for 10 min) increased peptic and tryptic hydrolysis of WPC, while heat-treatments > 70 ºC for 15 min also have a positive effect on the rate of hydrolysis of WPI that may be associated with differing aggregation phenomena (O'Loughlin, Murray, Kelly, FitzGerald & Brodkorb, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For β-cas, the relatively low molar sequence coverages in two parts of the sequence, i.e. and [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], might be due to the fact that these peptides contain phosphoserines. Yet it has been reported that phosphorylated peptides are typically not well ionised 32, 33 .…”
Section: Towards Predicting Bovine Tryptic Hydrolysis 51mentioning
confidence: 99%
“…In addition, chemical modifications on the enzyme might affect the enzyme secondary specificity. For instance, modifying lysine residues in bovine trypsin by succinylation led to a 8-10 times higher acceptance of positively charged AAs (KR) on the P1' position of the binding site sequence, while the modification by guanylation showed no effects 36 .…”
mentioning
confidence: 99%
See 1 more Smart Citation